RANCANG BANGUN GAME VIRTUAL REALITY BERTEMA BERBURU BINATANG DENGAN TOKOH PEMANAH BERBASIS ANDROID - Aditya, Muhammad Farid; Basri, Asril (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2019)
Multimedia allows computer users to get output in a richer and more attractive form compared to other print or electronic media such as newspapers or radio. The progress of computer multimedia to present information is very visible, because it is presented in the form of multimedia elements such as: sound, text, graphics, video, and animation which are expected to be more interactive, so that the information displayed is not only limited to the text model but is combined of these multimedia elements, so users are more interested in seeing the information presented.The purpose of making this application is to build a Hunting Game application with archers, this application runs stand alone / stand alone, and can not use the network. Application testing is carried out using the black-box-testing method and the results obtained by the application can run well in accordance with the functional objectives created. Evaluation of the application of 10 respondents using a questionnaire gets very good results with the final results of good value calculations.